Dysfunctional families and crime: righting wrongs - Kamaruddin, Zaleha (Pluto Journals, 2011)
The number of youths involved in crime and who show disregard for law and order is on the rise. What is more disturbing is the rise of violent crimes committed by them. The author argues that these concerns need to be addressed seriously. Pertinent questions need to be answered to understand the underlying reasons. This article is divided into three parts: the ﬁrst part deﬁnes dysfunctional families and their relationship with crime and some home-truths relating to them. The second emphasises the importance of knowledge and the inculcation of good values to individuals through the family. In the ﬁnal part some recommendations are made.